British and Irish newspapers implicitly support single-use masks over reusable face coverings - Augé, Anaïs; Tenbrink, Thora; Spear, Morwenna; Abrams, Nathan (Frontiers in Communication, 2023)
The environmental impact of waste caused by single-use masks or face coverings is an under-considered effect associated with the COVID-19 pandemic. Our study demonstrates how the discourse in British and Irish newspapers in the March 2020-December 2021 time frame relates to this problem. The combination of the protective purpose of face masks and their potential environmental impacts through littering or waste management means the wearing of face masks is simultaneously associated with the health crisis and creation of a new environmental challenge, combining two strands of journalism. By a combination of quantitative and qualitative discourse analysis, we identify concepts commonly associated with the terms "face-covering" and "mask", particularly concerning whether they refer to a disposable or reusable item. Results suggest that the newspaper discourse generally favoured references to single-use surgical masks. Newspapers reported on the environmental impact of face masks only in very limited ways. We propose that the increase in waste caused by face masks can be related to prevailing representations of single-use surgical masks and limited attention paid to environmental concerns.